1996
DOI: 10.1007/s0021663550336
|View full text |Cite
|
Sign up to set email alerts
|

LEAFS determination and concentration of metals in Great Lakes ecosystem

Abstract: A Laser-Excited Atomic Fluorescence Spectrometric (LEAFS) method for Tl determination has been extended to investigate the direct determination (without preconcentration nor acid digestion) of total Pb, for which the method validation was successfully achieved by using a standard reference material as well as many spike recoveries of digested and undigested unfiltered water samples. The method was applied to study total and dissolved Pb in many water columns collected from different stations in Lake Ontario. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…3f) differ slightly, indicating some lateral heterogeneity. One profile shows that Tl is escaping to the overlying water, in agreement with porewater profiles from the Central Basin of L. Erie (Cheam et al, 1996) and for another unspecified site in the same lake (Cheam, 2001).…”
Section: Solid Phase Concentration Profilessupporting
confidence: 77%
See 1 more Smart Citation
“…3f) differ slightly, indicating some lateral heterogeneity. One profile shows that Tl is escaping to the overlying water, in agreement with porewater profiles from the Central Basin of L. Erie (Cheam et al, 1996) and for another unspecified site in the same lake (Cheam, 2001).…”
Section: Solid Phase Concentration Profilessupporting
confidence: 77%
“…Such an interpretation assumes that post-depositional mobility of Tl is negligible. Yet, the only two profiles of porewater Tl concentrations reported in the literature (Cheam et al, 1996;Cheam 2001) show sharp Tl peaks a few cm below the sediment-water interface that indicate post-depositional remobilization of Tl, its relocalization within the sediment column and its transport to the overlying water. The potential influence of diagenetic processes on the Tl sedimentary profiles has not been addressed to date.…”
Section: Introductionmentioning
confidence: 99%
“…were low, which suited the LEAFS system well, being able to analyze these waters directly without any pre-concentration. Using samples from a peeper, Cheam et al (1996c) reported the first genuine sediment pore water profile of Tl concentration ranging from sub-detection limit to 40 ng/L. The profile was characterized by a maximum below the watersediment interface, with concentration about three times greater than in the overlying water.…”
Section: Pore Watersmentioning
confidence: 99%
“…Masera et al (384) investigated matrix effects in the determination of Au, Ir, Pd, Pt, and Rh in silver nitrate by ETA-LEAFS. This technique was also used for the determination of Sn in nickel-base alloys (385), Hg in silver (386), Pb in blood (387), Tl (388) and Pb (389) in lake water, Au in air particulates (390), P in polymers by direct analysis of solid samples (391), Co in soil, steel, and graphite (392), Ge in water and blood (393), Bi in snow and ice (394), and Ir, Rh, Pd, Pt, and Au in water (395). A combined laser ablation-LEAFS technique was described for the determination of Na in water (396).…”
Section: Laser Techniquesmentioning
confidence: 99%